Strategi Dakwah KH. M. Hasyim Asy’ari dalam Menyebarkan Agama Islam di Indonesia 1899-1947 - Tarpin, Tarpin; Permana, Agus; Nurhasanah, Dedeh; Fajriudin, Fajriudin; Maman, Maman (UIN Sunan Gunung Djati Bandung, 2024)
K.H M. Hasyim Asy'ari is a scholar whose name is familiar in the archipelago. He is a scholar and at the same time a national hero because of his big role which was very influential in the independence of the Republic of Indonesia, progress and glory of the Islamic religion. The services he has rendered are enormous with great sacrifices. Among his great services was establishing the Tebuireng Islamic Boarding School in Tebuireng (1899-1947). The establishment of this Islamic boarding school was one of the greatest achievements he had made. He founded the Tebuireng Islamic Boarding School and began preaching for the benefit of the people. So what and what was his strategy in preaching to spread the religion of Islam? Therefore, this research was formulated and aims to find out how K.H Hasyim Asy'ari's preaching strategy was in spreading Islam in Tebuireng in 1899-1947. This research uses a historical research method which has four stages, namely heuristics, criticism, interpretation and historiography. The results of this research show that in preaching, K.H Hasyim Asy'ari used various strategies, such as building Islamic boarding schools, preaching bil kalam wa risaleh, establishing the Nadhatul Ulama (NU) organization, and Jihad Resolution. Apart from that, he also carried out special methods in preaching to fight for Indonesian independence. K.H Hasyim Asy'ari's achievements not only have an impact on the benefit of religion, but also have a big impact on maintaining the independence of the Republic of Indonesia to this day.